Implications for Nutrition Research from the National Academies' Report Reproducibility and Replicability in Science (P13-039-19). (13th June 2019) - Allison, David
Abstract: Objectives: To present the findings, conclusions, and recommendations of the National Academies report Reproducibility and Replicability in Science, as relevant to the nutrition research community, and to engage in a discussion of implications for nutrition research. Methods: The report was developed by a committee of individuals with expertise in research methodologies across a range to disciplines and fields, including nutrition research. The committee was charged with assessing what is known about the extent of the issues of replication and reproducibility (R&R) in scientific and engineering research. To inform the development of the report, the committee held several evidence-gathering sessions and reviewed published literature. Results: Reproducibility and Replicability in Science will be published in spring 2019, after undergoing the National Academies' rigorous review process. The report will include (1) definitions of "reproducibility" and "replication, " (2) an assessment of what is known about the extent of R&R in scientific and engineering research, (3) consideration of whether a lack of R&R impacts the health or the public's perception of research, (4) a review of approaches to improve R&R, (5) examination of factors affecting R&R, (6) consideration of R&R across a range of research methodologies, and (7) conclusions and recommendations for improving R&R and highlighting examples of good practices. Conclusions: Conclusions remain confidential until the report has cleared the National Academies report review process. The report will include conclusions and recommendations for improving R&R, with relevance for nutrition research. Funding Sources: This study was supported by the U.S. National Science Foundation and the Alfred P. Sloan Foundation.